2016
DOI: 10.1053/j.jrn.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Psoas Muscle Cross-sectional Area as a Measure of Whole-body Lean Muscle Mass in Maintenance Hemodialysis Patients

Abstract: Objective We investigate whether psoas or paraspinous muscle area measured on a single L4–5 image is a useful measure of whole lean body mass compared to dedicated mid-thigh magnetic resonance imaging (MRI). Design Observational study. Setting Outpatient dialysis units and a research clinic. Subjects 105 adult participants on maintenance hemodialysis. No control group was used. Exposure variables Psoas muscle area, paraspinous muscle area, and mid-thigh muscle area (MTMA) were measured by MRI. Main o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 22 publications
0
50
0
Order By: Relevance
“…Indeed, the study performed by Yang et al showed that a single assessment of mid‐thigh CSA performed at 50% of femur length by MRI correlates well with subcutaneous fat ( r = 0.98, P < 0.001), intermuscular fat ( r = 0.97, P < 0.001), and thigh muscle volume ( r = 0.97, P < 0.001) measured by MRI, allowing speeding up volume quantity MRI assessment. These results were confirmed by the study performed by Morrell et al, who showed that lean body weight values estimated by dual‐energy absorptiometry significantly correlates with CSA of psoas muscle ( r = 0.74, P < 0.001), paraspinous muscle ( r = 0.58, P < 0.001), and mid‐thigh muscles ( r = 0.81, P < 0.001) measured on a single MRI slice.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, the study performed by Yang et al showed that a single assessment of mid‐thigh CSA performed at 50% of femur length by MRI correlates well with subcutaneous fat ( r = 0.98, P < 0.001), intermuscular fat ( r = 0.97, P < 0.001), and thigh muscle volume ( r = 0.97, P < 0.001) measured by MRI, allowing speeding up volume quantity MRI assessment. These results were confirmed by the study performed by Morrell et al, who showed that lean body weight values estimated by dual‐energy absorptiometry significantly correlates with CSA of psoas muscle ( r = 0.74, P < 0.001), paraspinous muscle ( r = 0.58, P < 0.001), and mid‐thigh muscles ( r = 0.81, P < 0.001) measured on a single MRI slice.…”
Section: Resultsmentioning
confidence: 99%
“…Of 67 records identified through search query and two identified through other sources, 45 were excluded from title and abstract, while the remaining 24 were downloaded for a deeper assessment. Finally, a total of 18 articles matched the topic at issue …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations